Agenesis of the fetal corpus callosum: sonographic signs change with advancing gestational age. (December 2013) - Paladini, D.; Pastore, G.; Cavallaro, A.; Massaro, M.; Nappi, C.
ABSTRACT Objectives To assess the presence and degree of indirect signs of agenesis of the corpus callosum (ACC) according to gestational age and determine the percentage of cases in which each sign is present by 24 gestational weeks. Methods We analyzed retrospectively 54 cases of ACC which underwent three‐dimensional neurosonography at our unit between January 2005 and December 2012. A single examination was available in 48 cases and six cases were followed up longitudinally, giving a total of 69 examinations. The following variables were assessed: indication for referral, karyotype, width of the atrium and presence/absence of colpocephaly, the cavum septi pellucidi, dorsal cyst and additional central nervous system (CNS) and non‐CNS anomalies. Results Overall, there were 31 cases of complete ACC (cACC, 42 examinations) and 23 cases of partial ACC (pACC, 27 examinations). The mean gestational age was lower in the cases referred because of anomalies other than ACC than it was in those referred because of ventriculomegaly and/or suspicion of ACC (P < 0.05). Atrial width showed a positive linear correlation with advancing gestational age (P < 0.0001); it was < 10.0 mm in 25/34 (73.5%) examinations < 24 gestational weeks and in 9/35 (25.7%) ≥ 24 weeks (P < 0.001). Colpocephaly was present in 20.6% (7/34) of examinations < 24 weeks and in 68.6% (24/35) of those after 23 weeks (P < 0.05). The cavum septi pellucidi was present and visible at least in part in 17 (63%) of the 27 pACC examinations. In nine of the 27 (33.3%) pACC examinations, there was neither ventriculomegaly nor absence of the cavum septi pellucidi. Associated anomalies were present in 25/54 (46.3%) cases, and in 11 these included or consisted of CNS abnormalities. Karyotype was abnormal in seven of the 40 (17.5%) cases in which it was available. Conclusions In a significant proportion of cases, most of the indirect signs of ACC are either absent or barely visible at the time of the midtrimester screening ultrasound examination. Therefore, ACC may escape diagnosis at midtrimester screening ultrasound. In particular, a third of examinations in fetuses with pACC may not show any abnormality in the transventricular screening view < 24 weeks. The medicolegal implications of such findings are important and should be considered. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.